The Relationship Between Risk Factors And Hearing Loss In Infants With Otoacoustic Emissions (Cuestiones de Fisioterapia, 2025)
Background: Hearing loss is a common disorder that frequently affects newborns. Hearing screening innewborns is a program to reduce the number of hearing loss events worldwide. In addition, OtoacousticEmissions (OAEs) are objective screening tools in newborns. This study aimed to determine the relationshipbetween risk factors and hearing loss in infants with hearing screening otoacoustic emissions.Subjects & Methods: This study uses an analytic retrospective study designed by taking secondary data frommedical records of infants at Dr. Soetomo Hospital for five years (2017-2021). The inclusion criteria for thestudy sample were infants under one-year, complete medical records, infants with risk factors and normal, andinfants who had been screened for hearing with the first stage of Otoacoustic Emissions